MODEL STOKASTIK PADA PERTUMBUHAN EKONOMI DI KABUPATEN KARO - Ferdinand Sinuhaji; Juli Loisiana Butarbutar (Universitas Quality, 2019)
The purpose of this research is to compile a model of economic growth in Karo District with stochasticity so that it can predict the amount of economic growth in the future Karo District. The research method with data analysis uses a model that was built to be applied to analyze economic growth in Karo District and compose a model with mathematical assumptions that will be applied into the model.The results of the study are the estimation of the Karo Regency GRDP based on the constant 2010 prices according to the forthcoming expenditure of karo district in 2019, which is 14.22521 trillion Rupiahs and a year later or unknown is 14.72309 trillion Rupiahs and the estimation of the amount of economic growth in the Karo district in 2019 to come at 4.95%.A year later the estimated economic growth of Karo district was estimated at 3.49%. Conclusion The estimated value of population growth from the model made in 2011, 2012, 2013, 2014, 2015, 2016, 2017, 2018 is close to the actual population growth value with a MAPE value of 4.9590%.